PEMBUATAN SABUN DENGAN MENGGUNAKAN KULIT BUAH KAPUK (Ceiba petandra) SEBAGAI SUMBER ALKALI - Lilis Sukeksi; Andy Junianto Sidabutar; Chandra Sitorus (Talenta Publisher (Universitas Sumatera Utara), 2017)
The purpose of this study is to examine the effect of reaction time and temperature toward the formed of soap product. This study begins by drying the skin of cotton and burning to gain the ash of cotton fruit skin. The combustion is done by using muffle furnace at 500 oC for 3 hours. Then, extraction is done on ash by using aquadest with a ration 1:3 to obtain alkali. This alkali will be used with cooking oil from palm in saponification process with fixed volume variable oil of 30 ml, velocity of stirring is 250 rpm, and oil volume : alkali volume 1:2 (ml). Whereas for the free variable are reaction temperature at 60 oC, 70 oC, 80 oC, stirring time at 60 minutes, 90 minutes, 120 minutes. The observed responses are density, acidity (pH), saponification number and free alkali. The best results were obtained at 80 °C and stirring time of 120 minutes with a density of 1.34 gr / ml, pH 9.1, saponification number of 200.349 and a 0.07% free alkali content.